(untitled) (Research, Society and Development, 2022)
Education was, in the past, able to adjust to changing circumstances and thus provide some basis; but present change is not like past changes and the art of living in an information-saturated world still has to be learned. Thus, the purpose of this study was to relate education in liquid modernity and the challenge of educating. The powerful flow from solid modernity to liquid modernity presaged new social changes previously unknown in scope and speed is creating unprecedented new conditions in which individuals must pursue their fragmented goals. Education in the past has taken many forms and has proven capable of adjusting to changes and circumstances by setting new goals and designing new strategies. Transferring to individual students the responsibility for the composition of the teaching/learning trajectory reflects the increasing reluctance of students to make long-term commitments that restrict the range of future options and limit the room for maneuver. Among the conspicuous effects of de-institutionalizing pressures are the "privatization" and "individualization" of teaching-learning environments and situations, as well as a gradual but relentless replacement of the orthodox teacher-student relationship with the vendor-client, or shopping-standard mall shopping. This is the social scenario in which today’s educators are bound to operate.